2013
DOI: 10.1371/journal.pone.0057479
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Multidimensional Optimization of an Asymmetric Bispecific IgG Antibody Mimicking the Function of Factor VIII Cofactor Activity

Abstract: In hemophilia A, routine prophylaxis with exogenous factor VIII (FVIII) requires frequent intravenous injections and can lead to the development of anti-FVIII alloantibodies (FVIII inhibitors). To overcome these drawbacks, we screened asymmetric bispecific IgG antibodies to factor IXa (FIXa) and factor X (FX), mimicking the FVIII cofactor function. Since the therapeutic potential of the lead bispecific antibody was marginal, FVIII-mimetic activity was improved by modifying its binding properties to FIXa and FX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
312
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(317 citation statements)
references
References 46 publications
4
312
0
1
Order By: Relevance
“…15 Although the pharmacological concept was clearly demonstrated by hBS23, further optimization to improve FVIII-mimetic cofactor activity, PK, immunogenicity, physicochemical stability, and manufacturability resulted in ACE910, a humanized bispecific antibody with multidimensionally optimized properties. 16 The hemostatic activity of ACE910 was demonstrated in a primate model of acquired hemophilia A, 17 and weekly subcutaneous doses of ACE910 at 1 mg/kg in a longterm primate model significantly reduced spontaneous joint bleeds, The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…15 Although the pharmacological concept was clearly demonstrated by hBS23, further optimization to improve FVIII-mimetic cofactor activity, PK, immunogenicity, physicochemical stability, and manufacturability resulted in ACE910, a humanized bispecific antibody with multidimensionally optimized properties. 16 The hemostatic activity of ACE910 was demonstrated in a primate model of acquired hemophilia A, 17 and weekly subcutaneous doses of ACE910 at 1 mg/kg in a longterm primate model significantly reduced spontaneous joint bleeds, The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%
“…Emicizumab is a recombinant humanized bispecific monoclonal antibody that acts as an FVIII mimetic by binding simultaneously to activated factor IX (FIXa) and factor X (FX). 18,19 Because of its unique structure, emicizumab is not expected to induce FVIII inhibitor development or be affected by existing FVIII inhibitors. Subcutaneously administered emicizumab showed high bioavailability in cynomolgus monkeys, 20 and once-weekly administration significantly reduced spontaneous bleeding symptoms in a primate model of acquired hemophilia A.…”
Section: Introductionmentioning
confidence: 99%
“…24 The new therapeutic alternative for patients with inhibitor is a humanized bispecific antibody that binds to and bridges activated factor IX (factor IXa) and factor X, thereby acting as a factor VIII-mimetic agent. 25,26 Emicizumab has a unique structure and it is not affected by factor VIII inhibitors. Moreover, clinical trials results showed that this product is safe and a single weekly subcutaneous administration has the potential to reduce or prevent bleeding episodes in patients with severe hemophilia A with or without factor VIII inhibitors.…”
Section: Recombinant Factor VIII Productsmentioning
confidence: 99%